COVID‐19 in DMARD‐treated patients with inflammatory rheumatic diseases: Insights from an analysis of the World Health Organization pharmacovigilance database. (25th May 2021) - Dernoncourt, Amandine; Schmidt, Jean; Duhaut, Pierre; Liabeuf, Sophie; Gras‐Champel, Valérie; Masmoudi, Kamel; Bennis, Youssef; Batteux, Benjamin
Abstract: Background: To determine whether the use of disease‐modifying antirheumatic drugs (DMARDs) is linked to the risk of COVID‐19 among patients with inflammatory rheumatic diseases (IRDs). Methods: We performed a disproportionality analysis of the World Health Organization pharmacovigilance database between January 1, 2020, and June 10, 2020. The frequency of COVID‐19 reports for all DMARD classes identified was compared with that for all other reports for all other drugs and quoted as the reporting odds ratio (ROR) (95% confidence interval [CI]). Results: Among 980, 446 individual case‐safety reports voluntarily recorded in the database, 398 identified COVID‐19 in DMARD‐treated patients with IRDs. There were 177 (44.5%) patients with rheumatoid arthritis (RA), 120 (30.1%) with ankylosing spondylitis (AS), 93 (23.4%) with psoriatic arthritis (PsA), and 8 (2.0%) with juvenile idiopathic arthritis. Most of the cases of COVID‐19 occurred in patients taking anti‐TNF agents (84.2%), resulting in a significant disproportionality signal (ROR [95% CI]: 8.31 [7.48–9.23]) – particularly in patients with RA, AS or PsA. A significant inverse disproportionality was found for the anti‐IL‐6 agent tocilizumab (ROR [95% CI]: 0.12 [0.02–0.88]) and JAK inhibitors (ROR [95% CI]: 0.33 [0.19–0.58]) in patients with RA – suggesting that these two drug classes are safer in the context of RA. Conclusion: Our results are in line with the literature on a potentially better safety profile for anti‐IL‐6 agents and JAK inhibitors. The WHO pharmacovigilance data suggest that COVID‐19 is significantly more frequent in patients with IRDs treated with TNF inhibitors.